Modeling and Implementation of a Specific Microprocessor to Enhance the Performance of PLCs Employing FPGAs - Delgado-del-Carpio, Marcelo; Hilario-Tacuri, Alexander; Hernández-Gutiérrez, Carlos A. (Journal of Electronics and Electrical Engineering, 2023)
This work presents the design of a microprocessor synthesized in FPGA based on the IEC 61131-3 standard. We report the architecture, and the operation of the internal hardware which allows the execution of Instruction List (IL). One of the most important components is the operands_selector block which allows memory elements, inputs, or outputs of the microprocessor to be treated as operands. Two ALUs are available to perform a bit, integer, and floating-point operations. The implementation of this microprocessor allows concluding that our designed microprocessor implemented in xc7a100tcsg324 (Xilinx) or EP4CE10E22C8 (Intel) FPGAs is superior in their execution times compared to the microprocessor evaluated in early studies and to one of the S7-1500 family processor.